Counseling goals of athletes during injury rehabilitation: a descriptive analysis - Schlierf, J. R.; Jaskiw, T. S.; Brewer, B. W.; Van Raalte, J. L. (Journal of Clinical Sport Psychology, 2024)
Although goal setting is widely recommended for sport injury rehabilitation, little is known about the content of the goals set by athletes with injuries. Toward this end, a qualitative content analysis was performed on the goals and barriers to goal attainment identified by 163 intercollegiate student athletes (117 men and 46 women) participating in counseling interventions during sport injury rehabilitation. Most of the 956 goals set (84%) contained a physical element. A physical barrier was identified for 49% of the goals. Economic, cognitive, emotional, and social elements were noted as both goals and barriers. Goal content did not change significantly over the course of rehabilitation. Most goals were specific, process, short term, and positively phrased. The findings provide a detailed description of the types and qualities of counseling goals set by athletes during injury rehabilitation, offering professionals insight into the wide range of concerns expressed by athletes with injury during counseling.